(untitled) (Al-Aasar, 2026)
Lala Sehrai is recognized as a dignified and influential figure in the landscape of Urdu Naat literature, who set a practical example of dedicating his entire literary life to the praise and glorification of the Holy Prophet (peace and blessings of Allah be upon him). He is among those writers for whom Naat is not just a literary genre but a beautiful blend of spiritual attachment, intellectual responsibility and heartfelt devotion. During his long creative journey, he also experimented in various literary fields, but the main and dominant direction of his speech gradually turned towards Naat. Especially in the last part of his life, his entire attention was focused on the cultivation, promotion and development of this sacred genre The main source of Lala Sehrai’s Naatiya poetry is her immense love for the Holy Prophet (peace and blessings of Allah be upon him) and her deep heartfelt attachment to his message of guidance. This same passionate passion is both the soul and the real strength of her poetry. However, her uniqueness lies in the fact that instead of expressing this love on a purely emotional level, she harmonized it with conscious insight and intellectual balance. She has an abundance of devotion to the fullest extent, but along with it, a serious intellectual awareness and a balanced perspective are also visible.